Dispersal in a patchy landscape reveals contrasting determinants of infection in a wild avian malaria system. - Knowles, S; Wood, M; Alves, R; Sheldon, B (2013)
Understanding exactly when, where and how hosts become infected with parasites is critical to understanding host-parasite co-evolution in natural populations. However, for host-parasite systems in which hosts or parasites are mobile, for example in vector-borne diseases, the spatial location of infection and the relative importance of parasite exposure at successive host life-history stages are often uncertain. Here, using a 6-year longitudinal data set from a spatially referenced population of blue tits, we test the extent to which infection by avian malaria parasites is determined by conditions experienced at natal or breeding sites, as well as by postnatal dispersal between the two. We show that the location and timing of infection differs markedly between two sympatric malaria parasite species. For one species (Plasmodium circumflexum), our analyses indicate that infection occurs after birds have settled on breeding territories, and because the distribution of this parasite is temporally stable across years, hosts born in malarious areas could in principle alter their exposure and potentially avoid infection through postnatal dispersal. Conversely, the spatial distribution of another parasite species (Plasmodium relictum) is unpredictable and infection probability is positively associated with postnatal dispersal distance, potentially indicating that infection occurs during this major dispersal event. These findings suggest that hosts in this population may be subject to divergent selection pressures from these two parasites, potentially acting at different life-history stages. Because this implies parasite species-specific predictions for many coevolutionary processes, they also illustrate the complexity of predicting such processes in multi-parasite systems.